Record-breaking racing cars Kharkiv national automobile and highway university (laboratory of racing cars KhAHI) : popular science handbook of racing cars - Turenko, A. M.; Klymenko, V. I.; Lukashev, I. V.; Chernysov, O. O.; Туренко, А. М.; Клименко, В. І.; Лукашев, І. В.; Чернишов, О. О. (Харківський національний автомобільно-дорожній університет, 2023)
KhADI cars are famous throughout the world. The process of designing cars involves both professional designers and enthusiastic students. At different periods of time various types of cars were assembled on the assembly rig of the KhAHI such as sport and touristic cars, electric cars, record-racing cars as well as a cryomobile and an ecoautomobile. More than one record has been beaten by these cars. Due to the KhADI cars Ukraine is a worthy competitor at the international competition «Shell eco-marathon». The publication is intended for the general reader: both professionals and people who are fond of motor sports.
Швидкісні автомобілі Харківського національного автомобільно-дорожнього університету (лабораторія швидкісних автомобілів ХАДІ) : науково-популярний довідник з швидкісних автомобілів
Keywords: KhADI cars; automobiles; vehicles; sport and touristic cars; electric cars; record-racing cars; cryomobile; ecoautomobile; автомобілі ХАДІ; автомобілі; транспортні засоби; спортивно-туристичні автомобілі; електромобілі; рекордно-гоночні автомобілі; кріомобіль; екоавтомобіль; 629.371.21(085)